Un modelo cognitivo para la clasificación de los complementos directos afectados en español - Cuartera Otal, Juan (Wydawnictwo Naukowe Uniwersytetu im. Adama Mickiewicza w Poznaniu, 2004)
This article tries to justify an extended typology of the category "affected object1, analyzed by applying prototypical features and compared to other well-known versions (Anderson, 1977; Roberts, 1987 or Demonte, 1991). These data allow us to reflect about some combinatorial characteristics of Spanish verbs containing affected arguments in their argument structures, e. g. telicity of constructions (Tenny, 1987) or affectedness constraints (Jaeggli, 1986).
A Cognitive Model for the Classification of Affected Objects in Spanish